Improved quality signaling boosts farmers' willingness to pay for quality assured cassava planting materials: evidence from experimental auctions in the Lake Zone of Tanzania - Msami, Jessey A.; Nickas, Jonas; Kihimba, Hemed A.; Nkwabi, James J.; Legg, James P. (Frontiers in Sustainable Food Systems, 2025)
Cassava (Manihot esculenta Crantz) is a key staple food in the Lake Zone of northwestern Tanzania and a critical food security crop in Sub-Saharan Africa. However, rather than purchasing quality assured cuttings of improved varieties from trusted sources, many farmers rely on free or almost free cassava cuttings from unregulated sources to establish their plots. This study uses Vickrey's method to examine farmers' willingness to pay for cassava cuttings by exploring two aspects in two rounds of experimental auctions: Round 1, the impact of asymmetric information between buyers and sellers, and Round 2, the influence of enhanced quality signaling using quality assurance labels. Cassava farmers (n=200) placed bids on three products: P1, a farmer-sourced landrace; P2, an improved variety called TARICASS4 sourced from a quality declared seed (QDS) producer; P3, the TARICASS4 variety, also sourced from a QDS producer, but with a quality assurance label. In Round 1, the mean bids per cutting did not differ between treatments, and were TSh 24.5 (USD 0.0091) for P1, TSh 23.4 (USD 0.0087) for P2 and TSh 24.6 (USD 0.0091) for P3. This changed in Round 2, where the mean bids per cutting were TSh 11.5 (USD 0.0043) for P1, TSh 20.0 (USD 0.0074) for P2, and TSh 32.7 (USD 0.012) for P3. Despite P2 and P3 being the same variety and sourced from QDS producers, bidders in Round 2 placed a premium price on P3 because of the added quality assurance label. Relative to bids for the local landrace in Round 2, bids were almost double for the improved variety, and almost triple for the improved variety with certification labeling. These results confirm that providing product information and enhancing quality signaling can significantly boost farmers' willingness to pay for cassava seed, thereby increasing demand. This will have the important consequence of enhancing the commercial viability and therefore sustainability of the cassava seed system.